Season effects on the suckling behavior of piglets - Moreira, Rennan H. R.; Oliveira, Rodrigo F. [UNESP]; Palencia, Jorge Y. P.; Fonseca, Leonardo S.; Garbossa, Cesar Augusto P.; Abreu, MArvio L. T.; Ferreira, Rony A. (Acad Brasileira De Ciencias, 2020)
The suckling behavior of piglets was evaluated in summer and winter, using 21 sows of the same genetic line. Data were collected in July (winter) and in January (summer). The experimental design was a randomized complete block (age of piglets) in a 2x2 factorial scheme, with season of the year (winter and summer) and shift (day, from 06 h to 1h:59min and night from 18h to 05h:59min) as factors. The behavioral variables analyzed were number, interval, and frequency of suckling. The behaviors were monitored on day 7 and 15 of lactation, for 24 hours. In winter, the farrowing room had a mean temperature of 20.32 +/- 2.17 degrees C and a relative humidity (RH) of 58.63 +/- 2.99%. In the summer, the mean temperature was 26.65 +/- 4.02 degrees C, with an RH of 62.22 +/- 12.06%. During winter, the piglets presented longer sucklings during the night, dedicating 1.84 minutes more to suckling compared to the daytime. Nighttime sucklings were 3.13 minutes longer in winter than in summer. However, in summer, piglets suckled more often during the night, with greater interval between feeds during the day. Based on our results, the season influences the suckling behavior of piglets, with shorter feedings and greater frequencies in summer.
Keywords: Litter; number of suckles; suckling interval; suckling length; lactation; swine